Exclusive: Financial impact Of COVID-19 on Australian athletes - Warren, J. (2021)
In an exclusive interview with Ministry of Sport, CEO of the Australian Sports Foundation (ASF), Patrick Walker, outlined the findings in his organisation`s study into the impact of COVID-19 on Australian athletes seeking to make it professionally. The results are summarized here.